1989
DOI: 10.1007/bf01536325
|View full text |Cite
|
Sign up to set email alerts
|

Orocecal transit delay in obese patients

Abstract: Orocecal transit time was assessed with lactulose hydrogen breath test in 12 obese patients during intravenous infusion of placebo or naloxone 40 micrograms/kg/hr given in randomized order and in double-blind conditions. Transit time was also evaluated in 22 healthy controls. Orocecal transit was significantly (P less than 0.01) longer in the obese patients, during placebo treatment (median 130, range 100-200 min) than in the healthy controls (median 75, range 40-170 min). Compared with placebo, transit time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 26 publications
0
17
1
Order By: Relevance
“…We were careful, therefore, to match our patients, not only for gender but also for age. Obesity and, especially, morbid obesity, is known to predispose to SIBO [16,17]. While we did not include any morbidly obese patient (the highest BMI being 35.6 kg/m 2 ), and although we attempted to match NASH patients and controls for BMI, we failed to achieve this and the NASH group, not surprisingly, had a significantly higher BMI, a factor that may have contributed to the observed differences in LHBT results.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…We were careful, therefore, to match our patients, not only for gender but also for age. Obesity and, especially, morbid obesity, is known to predispose to SIBO [16,17]. While we did not include any morbidly obese patient (the highest BMI being 35.6 kg/m 2 ), and although we attempted to match NASH patients and controls for BMI, we failed to achieve this and the NASH group, not surprisingly, had a significantly higher BMI, a factor that may have contributed to the observed differences in LHBT results.…”
Section: Discussioncontrasting
confidence: 54%
“…Small intestinal bacterial overgrowth (SIBO) has been reported to coexist with NASH [7][8][9][10][11][12][13][14] and it has been suggested that liver injury and fibrosis could be, at least in part, related to exposure to bacterial products, and especially endotoxin, of intestinal origin. Furthermore, a number of factors common among NASH patients may predispose to SIBO [15]: obesity [16,17], advancing age [18], the use of anti-secretory drugs [19], and the presence of altered intestinal motility [10]. However, while both delayed small intestinal transit [10,20] and abnormal small intestinal motor patterns [21][22][23] have been described in chronic liver disease, it is unclear whether, in this situation, intestinal transit delay is a cause [20,24] or consequence [14,15] of SIBO.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, an increase in orocecal transit time (OCTT) was found [19], however this observation was not confirmed by subsequent studies [20,21].…”
Section: Introductionmentioning
confidence: 95%
“…Persons with a body mass index over 30 kg/M2 were also excluded because transit may be altered in clinically obese patients. [35][36][37] In addition women must have had a regular menstrual cycle for the last six months, the length needed to be 28±4 days and there had to be no major symptoms during the menstrual cycle. Excluded also were lactating women and those with a pregnancy within the last year.…”
Section: Experimental Subjectsmentioning
confidence: 99%